2008
DOI: 10.1007/s11095-008-9769-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Pegylated Dendrimeric Nanocarrier for Pulmonary Delivery of Low Molecular Weight Heparin

Abstract: Pegylated PAMAM dendrimer could potentially be used as a carrier for pulmonary delivery of LMWH for the long-term management of DVT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 30 publications
0
51
2
Order By: Relevance
“…The chemical structures of polymers for polymeric nanoparticles used in pulmonary delivery systems are shown Figure 2. 26,29,38,39,[54][55][56][57]59,61,69,70,74,75,[79][80][81][82][83][84][85][86][87][88][89][90][91][92][93] Due to their biocompatibility, surface modification capability, and sustained-release properties, polymeric nanoparticles are intensively studied using various important pulmonary drugs. These pulmonary drug include antiasthmatic drugs, 22,26 antituberculosis drugs, 38,39 pulmonary hypertension drugs, 29 and anticancer drugs.…”
Section: Drugs For Inhalationmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical structures of polymers for polymeric nanoparticles used in pulmonary delivery systems are shown Figure 2. 26,29,38,39,[54][55][56][57]59,61,69,70,74,75,[79][80][81][82][83][84][85][86][87][88][89][90][91][92][93] Due to their biocompatibility, surface modification capability, and sustained-release properties, polymeric nanoparticles are intensively studied using various important pulmonary drugs. These pulmonary drug include antiasthmatic drugs, 22,26 antituberculosis drugs, 38,39 pulmonary hypertension drugs, 29 and anticancer drugs.…”
Section: Drugs For Inhalationmentioning
confidence: 99%
“…138 Several studies have been published regarding pulmonary applications of dendrimers as systemic delivery carriers for macromolecules. 74,75,93,139 Kukowska-Latallo and colleagues 93 investigated the ability of polyamido amine (PAMAM) dendritic polymers (dendrimers) to augment plasmid DNA gene transfer in vivo and evaluates the targeting of the lung by alternative routes of administration. They suggested that vascular administration seemed to achieve expression in the lung parenchyma, mainly within the alveoli, while endobronchial administration primarily targeted bronchial epithelium, indicating that each delivery route requires different vectors to achieve optimal transgene expression, that each approach appears to target different cells within the lung.…”
Section: Dendrimer-based Nanoparticles For Lung Deliverymentioning
confidence: 99%
“…To this end, a handful of reports describing the application of highly branched molecules termed ''dendrimers'' have been reported in the literature. Dendrimers possess a range of attractive features such as multi-valency, nano-size, spherical architecture, surface-functional groups, low polydispersity and precise molecular weight, all of which render them versatile vectors in drug delivery (El-Sayed et al, 2002; Kannan et al, 2005;Vandamme & Brobeck 2005;Bai & Ahsan, 2009;Menjoge et al, 2010). Of the few reports available on the application of dendrimers for skin-mediated delivery of therapeutics, poly(amidoamine) (PAMAM) dendrimers have been among the most widely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Biocompatibility of the most PAMAM, Poly(lysine) dendrimers with cytotoxic (cationic) surface charged groups are improved to anionic surface with the aid of PEGylation, anionic amino acid such as glutamate over their cationic surface functionalities [22][23][24]. Despite successful talk on drug encapsulation and the biocompatibility of dendrimers, the fate of dendrimer is to readily degrade from the body as a non-toxic product after its administration [25].…”
Section: Introductionmentioning
confidence: 99%